A Needs-Based Curriculum Review for Diploma in Pharmacy Programme at a Malaysian University - Long CM, Lee WL, Iylia RR & Aishah A; Hadi MA (Archives of Global Professionals, 2011)
Programmed, systematic and structured curriculum review isessential to ensure quality professional education. Curriculumevaluation enables the institution to validate the compliance ofdidactic and experiential strategies with the current needs andfuture demand of the profession. The four conceptions ofcurriculum as highlighted by Ewell namely designedcurriculum, expectational curriculum, delivered curriculumand the experienced curriculum must be evaluated for aneffective curriculum review [1]. Involvement of stakeholders incurriculum review is essential.In Malaysia, Universiti Teknologi MARA (UiTM) is the onlypublic sector university together with 19 private collegesoffering a three year (six-semester) Diploma in Pharmacyaccredited by Malaysian Qualifications Agency (MQA)[2]. Theprogram was first started in 1996. The construct of first twoyears is didactic and laboratory practical based. However, inthe final year (3rd year) students are exposed to theexperiential hospital based training and research projects.Faculty of Pharmacy, UiTM reviews the curriculum every threeyears. In an attempt to develop a "Needs Based" curriculum across sectional survey was undertaken to assess knowledgeand skills required to become a competent Pharmacy assistant.Structured validated questionnaires were mailed torandomly chosen 8 hospitals across Malaysia along with adetailed cover letter explaining the purpose of the study. Thesample consisted of pharmacists and pharmacy assistants whowere willing to participate in the study.